La corrélation entre le Vietnamien et le Francais à travers les résultats d' études scolaires de ces deux matières : - Nguyễn, Thị Huệ Chi (Universite de Can Tho, 2010)
The purpose of my research aims to be able to well recognize the relationship between two languages in terms of linguistics. the distinction and diversity of these two languages help us to elaborate appropriate teaching methods to our audience in high school.